Evaluasi Penerapan Model Pembelajaran Meaningful Learning Berbasis TV Edukasi untuk Jenjang SMA - Kurniawati, Ika; Syamsul Hadi (Jurnal TEKNODIK, 2023)
Educational TV is a learning resource that is used especially during the Covid 19 pandemic. To maximize the use of Educational TV in the learning process, it is necessary to apply educational TV content-based learning models. One of the models developed is the Meaningful Learning Learning Model. This learning model is applied in high school level schools. To determine the effectiveness of the application of this learning model, it is necessary to evaluate its application. This research is an evaluation research. The evaluation approach used in this research is goal-oriented evaluation. The data collection method used is a combination of qualitative and quantitative, because the type of data collected is qualitative data and quantitative data. The targets (respondents) of this evaluation were Indonesian language teachers and SMAIT Nurul Fikri students with details of 30 students in class X MIPA 3, 31 students in class X MIPA 4, and 32 students in class X MIPA 2. The evaluation results show that the TV-based Meaningful Learning learning model is easy. applied. There is an increase in the quality of learning processes and products by applying the Meaningful Learning learning model based on Educational TV. The application of the TV Education-based Meaningful Learning learning model makes a significant contribution to solving learning problems. Thus it can be stated that the application of the TV-based Meaningful Learning learning model for learning at the high school level (SMA) is effective.